PENGARUH PENERAPAN MANAJEMEN RISIKO TERHADAP KINERJA KEUANGAN INDUSTRI PERBANKAN - Devica Pratiwi; Budi Kurniawan (Jurnal Akuntansi Bisnis, 2018)
The role of the large banking industry in the Indonesian economy affects banking governance, where prudence is strongly emphasized. Such caution is a reflection of the attitude of responsibility towards the trust given by the community. To address the risks involved in banking operations, risk management is a much-needed solution, which is used to identify, measure, monitor, and control risks arising from bank operations. This study takes independent variables in which NIM as a proxy of interest rate risk, NPL as proxy of credit risk, CAR as solvency & capital risk proxy, and LDR as a liquidity risk proxy. Dependent variable used in this research is financial performance of banking by using profitability ratio that is ROE. The sample of research selected by purposive sampling method get 12 companies that report 3 period of annual report that is year 2013, 2014, and 2015. Analyze technique which is done is by using multiple regression, and the analysis tool is SPSS version 21. The result show that NIM and CAR has significant influence on profitability, while NPL and LDR have insignificant influence.Keywords: risk management, bank performance indicator